Elicitation as a tool to improve the profiles of high‐value secondary metabolites and pharmacological properties of Hypericum perforatum. (19th May 2017) - Shakya, Preeti; Marslin, Gregory; Siram, Karthik; Beerhues, Ludger; Franklin, Gregory
Abstract: Objectives: In this review, we aim at updating the available information on the improvement of the Hypericum perforatum L. ( Hypericaceae ) phytochemical profile and pharmacological properties via elicitation. Key findings: Hypericum perforatum seedlings, shoots, roots, calli and cell suspension cultures were treated with diverse elicitors to induce the formation of secondary metabolites. The extracts of the elicitor‐treated plant material containing naphthodianthrones, phloroglucinols, xanthones, flavonoids and other new compounds were quantitatively analysed and tested for their bioactivities. While hypericins were mainly produced in H. perforatum cultures containing dark nodules, namely shoots and seedlings, other classes of compounds such as xanthones, phloroglucinols and flavonoids were formed in all types of cultures. The extracts obtained from elicitor‐treated samples generally possessed better bioactivities compared to the extract of control biomass. Summary: Although elicitation is an excellent tool for the production of valuable secondary metabolites in H. perforatum cell and tissue cultures, its exploitation is still in its infancy mainly due to the lack of reproducibility and difficulties in scaling up biomass production.